First record of Lissotrachelus ferrugineonotatus cricket producing ultrasound (Orthoptera: Grylloidea) - He, Zhu-Qing; Shen, Chu-Ze (Zootaxa, 2020)
The range of hearing for human is about 50 to 20,000 Hz, but some animals can produce ultrasounds over 20000 Hz. These include bats, cetaceans, rodents and even frogs (Feng et al., 2006). Katydids and crickets are famous singing insects belonging to order Orthoptera. Many katydids can produce ultrasounds even over 100 kHz (Montealegre-Z et al., 2006). However, the dominant frequency of most crickets ranges from 2 to 8 kHz (Walker & Carlysle, 1975; Robillard & Desutter-Grandcolas, 2004). In previous studies, only Eneopterinae crickets were reported to produce high-frequency songs (Robillard et al. 2007; Robillard & Tan 2013). We report that Lissotrachelus ferrugineonotatus crickets produce ultrasounds with peak at 26.25 kHz.